Preparation, Characterization and Biological Activity of New Derivatives of 3-Cyclic Oxazepine, 3-Cyclic Lactam and 3-Aminomethyl Imidazo (1, 2-a) Benzthiazol - Rana Abid Ali (Journal of Global Pharma Technology, 2018)
In this work a series of fourteen new compounds were synthesized. Compound [1] was formed from the reaction of 2-aminobenzothiazole and p-bromophenacyl bromide. Aldehyde group [2] was obtained from the reaction of compound [1] with pocl3 in presence of DMF and CHCl3 .After that shiff bases have been synthesized from the reaction of compound [2] with different aromatic amine to give new shiff bases [3-5]. These new shiff bases have been reduced to their corresponding amine [6-8] by means of sodium borohydride. Then reaction of shiff bases [3-5] with phenyl isocyanate gives 3-cyclic lactam derivatives [9-11]. 3-cyclic Oxazepine derivatives [12-14] were obtained by reaction of shiff bases [3-5] with succinic anhydride. These new formed compounds were diagnosed by12 C-NMR, 1H-NMR for some of them and FT-IR spectroscopy. Some of the prepared products have been studied their biological activities toward two kinds of bacteria. These products showed good efficacy to moderate toward bacteria.Keywords: Benzothiazole, Shiff bases, Lactam, Oxazepine, Biological activity.